Perception and Acceptability of Laboratory-Cultured Meat - Oluwatoyin Hannah Owokoniran; Gabriel Oluwole Owokoniran; Femi Peter Adesina; Imoleayo Sarah Olateju (ASEAN Journal of Science and Engineering Education, 2024)
This study aimed to determine the perception and acceptability of cultured meat in the Nigerian market. The investigation was conducted with the aid of a cross-sectional survey study using the online Google survey questionnaire platform. A total of 233 Nigerians responded to this research survey. The majority, 108 (46.4%), of the respondents were between 18–30 years old, and 150 (64.4%) were male. Almost half of the respondents (47.6%) have not heard or read about cultured meat before, and 208 (89.3%) have never tasted it. Gender (p = 0.003,  ᵪ2= 9.00) and whether respondents had tasted cultured meat before (p = 0.001,  ᵪ2= 13.45) were significant determinants of accepting cultured meat in Nigeria. Females were 2.31 times more likely (OR = 2.31, Cl = 1.33-4.01) to accept cultured meat than males, and those who had previously tasted cultured meat were 0.16 times less likely (OR = - 0.16, Cl = 0.05-0.47) to accept cultured meat. Component 1 of the principal components analysis (PCA) contains perceptions that cultured meat is unnatural, disgusting, unhealthy, or can lead to health complications in the future and a loss of balance in the ecosystem. Nigerians would be interested in consuming cultured meat if growing concerns about the resulting side effects on human health can be addressed.